A diverse assemblage of Permian echinoids (Echinodermata, Echinoidea) and implications for character evolution in early crown group echinoids. (18th April 2017) - Thompson, Jeffrey R.; Petsios, Elizabeth; Bottjer, David J.
Abstract: The Permian is regarded as one of the most crucial intervals during echinoid evolution because crown group echinoids are first widely known from the Permian. New faunas provide important information regarding the diversity of echinoids during this significant interval as well as the morphological characterization of the earliest crown group and latest stem group echinoids. A new fauna from the Capitanian Lamar Member of the Bell Canyon Formation in the Guadalupe Mountains of West Texas comprises at least three new taxa, including Eotiaris guadalupensis Thompson n. sp. an indeterminate archaeocidarid, and Pronechinus ? sp. All specimens represented are silicified and known from disarticulated or semiarticulated interambulacral and ambulacral plates and spines. This assemblage is one of the most diverse echinoid assemblages known from the Permian and, as such, informs the paleoecological setting in which the earliest crown group echinoids lived. This new fauna indicates that crown group echinoids occupied the same environments as stem group echinoids of the Archaeocidaridae and Proterocidaridae. Furthermore, the echinoids described herein begin to elucidate the order of character transitions that likely took place between stem group and crown group echinoids. At least one of the morphological innovations once thought to be characteristic of early crown group echinoids, crenulate tubercles, was in fact widespread in a number of stem group taxa from the Permian as well. Crenulate tubercles are reported from two taxa, and putative cidaroid style U-shaped teeth are present in the fauna. The presence of crenulate tubercles in the archaeocidarid indicates that crenulate tubercles were present in stem group echinoids, and thus the evolution of this character likely preceded the evolution of many of the synapomorphies that define the echinoid crown group.